Assessment of the Educational Environment of Major Clinical Wards in Educational Hospitals Affiliated to Hormozgan University of Medical Sciences Iran from the Perspective of Medical Students - Mehregan Heidari Hengami; Nadereh Naderi; Behjat Nasery (Kerman University of Medical Sciences, 2016)
Background & Objective: The educational environment has a fundamental role in the quality and efficiency of education The present study was undertaken to identify the perceptions of students on the educational environment in 4 major clinical wards at teaching hospitals affiliated to Hormozgan University of Medical Sciences Iran in 2014 Methods: In this descriptive crosssectional study educational environment was evaluated using the Dundee Ready Educational Environment Measure (DREEM) Sampling was conducted through census and the study population included all medical students (n = 184) passing their clinical courses in the internal pediatrics surgical obstetrics and gynecology wards in 3 hospitals affiliated to Hormozgan University of Medical Sciences Data were analyzed using ANOVA and Tukeys tests Results: The mean score achieved from the total 200 scores of the questionnaire was 10483 (524%) Although there was no significant difference between total scores of major clinical wards the pediatrics and obstetrics and gynecology wards obtained the highest lowest scores respectively No significant correlation was found between education and gender and the subscales of educational environment A significant difference was observed between major clinical wards in the subscale of teachers (P < 0001) Conclusion: The educational environment at clinical wards was considered as good by students Nevertheless problematic areas exist in all subscales of educational environment The obtained results can be utilized to better understand and resolve educational environment issues in Hormozgan University of Medical Sciences